Applying the Safety and Environmental Risk and Reliability Model (SERM) for Malaysian langat river collision aversion - Olanrewaju, O. S. (IGI Global, 2013)
Collision accident remains a big threat to coastal water transportation operation. Occurrence of a collision event exposes vessel owners and operators as well as the public to risk. The nature of the threat can be worrisome; it may lead to loss of life, damage to the environment, disruption of operation, and injuries. This makes hybrid analysis of accident frequency and consequence for risk quantification of accident scenarios through stochastic tools very imperative for reliable design and exercise of technocrat stewardship of safety and safeguard of the environmental. The study involves a predictive model for collision risk and mitigation option for aversion of collision incident. Accident frequency and consequence are obtained using probability tools. Validity of the result is checked with reliability tools. Findings of the study were checked with subsystem and uncertainty risk-contributing factors in order to arrive at a sustainable decision support for collision aversion for inland water transportation. This chapter discusses the result and validation of implementation of the Safety and Environmental Risk and Reliability Model (SERM) for aversion of collision accident for vessel navigating for inland waterways.